The determinants of house price behaviour in Asia Pacific countries / Nur Aiza Azmi - Azmi, Nur Aiza (Faculty of Business and Management, 2018)
The main purpose of this study is to determine the determinants of house price behaviour in Asia Pacific countries which is Australia, China, Hong Kong, Indonesia, Japan, Korea, Malaysia, New Zealand, Singapore and Thailand on yearly basis from year 2006 to 2015. There are six determinant relate with housing price which is Gross Domestic Product (GDP), Inflation (I), Interest Rate (IR), Household Saving (HS), Unemployment Rate (UR) and Household Debt (HD). These result further understanding about the relationship between Housing Price Behaviors and other variable. The result indicates that there are significantly related to house price using panel data. As result is GDP, Inflation Rate and Household Saving and Household Debt show significant positive relationship with house price. Otherwise, Interest Rate and Unemployment show significant negative towards house price. The paper is useful for investors, speculators, policies makers and buyers to know which factors to account for in housing investment decision. This paper can also serve as a guide for the government in stabilizing the residential housing price in Asia Pacific.